Effect of cosmetic contact lens on contrast sensitivity / Abdul Hafiz Abdul Muhimim - Abdul Muhimim, Abdul Hafiz (Faculty of Health Sciences, 2015)
In the recent decades, the number of cosmetic contact lens wearer had increased drastically, the number of complications was directly proportional to the number of the cosmetic contact lens wearer. The objective of this study was to determine how the cosmetic contact lens affecting the contrast sensitivity among the contact lens wearer especially cosmetic contact lens wearer. In this study, 24 subjects were recruited. In 24 subjects consisted of 12 clear contact lens wearer and 12 cosmetic contact lens wearer. Contrast sensitivity of each subjects were evaluated by using Pelli-Robson and Functional Acuity Contrast Test chart at 3, 6, 12, and 18 cycles per degree.The data was analyzed using SPSS version 22.0. The independent t-test analysis was used to compare the log contrast sensitivity findings between cosmetic and clear contact lens.The mean contrast sensitivity scores with clear and cosmeticcontact lensmeasured using F.A.C.T were p=0.048 for 3 c/d, p=0.042 for 6 c/d, p=0.040 for 12 c/d and p=0.008 for 18 c/d (p<0.05) and measured using Pelli-Robson was p=0.020 (p<0.05). In conclusion cosmetic contact lens causes reduction in contrast sensitivity as tested using FACT chart and Pelli-Robson chart.